Antioxidant and Anti-Diabetic Properties of Olive (Olea europaea) Leaf Extracts: In Vitro and In Vivo Evaluation - Hanem M. M. Mansour; Ashraf A. Zeitoun; Hagar S. Abd-Rabou; Hesham Ali El Enshasy; Daniel Joe Dailin; Mohamed A. A. Zeitoun; Sobhy A. El-Sohaimy (MDPI AG, 2023)
(1) Objective: The main objective of the current study was to evaluate in vitro and in vivo an antioxidant property of three genotypes of olive leaf extract (OLE) (picual, tofahi and shemlali), and furthermore to assess potential activity in the treatment and/or prevention of diabetes mellitus type II and related implications. (2) Methodology: Antioxidant activity was determined by using three different methods (DDPH assay, reducing power and nitric acid scavenging activity). In vitro α-glucosidase inhibitory activity and hemolytic protective activity were assessed for the OLE. Five groups of male rats were used in in vivo experiment for evaluating the antidiabetic potential of OLE. (3) Results: The genotypes of the extracts of the three olive leaves exhibited meaningful phenolic and flavonoids content with superiority for picual extract (114.79 ± 4.19 µg GAE/g and 58.69 ± 1.03 µg CE/g, respectively). All three genotypes of olive leaves demonstrated significant antioxidant activity when using DPPH, reducing power and nitric oxide scavenging activity with IC50 ranging from 55.82 ± 0.13 to 19.03 ± 0.13 μg/mL. OLE showed a significant α-glucosidase inhibition activity and dose-dependent protection from hemolysis. In vivo experimentation revealed that the administration of OLE alone and the combination of OLE+ metformin clearly restored the blood glucose and glycated hemoglobin, lipid parameters and liver enzymes to the normal level. The histological examination revealed that the OLE and its combination with metformin successfully repaired the liver, kidneys and pancreatic tissues to bring them close to the normal status and maintain their functionality. (4) Conclusion: Finally, it can be concluded that the OLE and its combination with metformin is a promising treatment for diabetes mellitus type 2 due to their antioxidant activity, which emphasizes the potential use of OLE alone or as an adjuvant agent in the treatment protocol of diabetes mellitus type II.